РЕГЛАМЕНТАЦИЯ НОРМ О ПРАВАХ ЧЕЛОВЕКА В ДОКУМЕНТАХ ЕВРОПЕЙСКОГО СОЮЗА И ДОКУМЕНТАХ ЕВРАЗИЙСКОГО ЭКОНОМИЧЕСКОГО СОЮЗА - Идрышева Сара Кимадиевна (World Science, 2019)
The article is devoted to the consideration of the main program documents on the establishment of the European Union and the Eurasian Economic Union, as well as its predecessors in terms of identifying the participants in these integration associations about the purpose of creating interstate unions. Based on the application of logical, historical methods of scientific research and comparative legal analysis of the texts of constituent documents of two subjects of international law, the author comes to the conclusion that there is such a lack of constituent documents of the Eurasian Economic Union as the lack of emphasis on ensuring well-being for each person living in the union states. The author believes that the prevalence in the constituent documents of the EAEU goals of achieving economic success entails an appropriate attitude to the degree of protection of human rights in this union.